Analytical survey of scenario for permanent method of contraception - Agarwal, Vandana; Mehani, Rekha; Jain, Swati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: This study has analysed the average completed family size with relation to parity, average age of both partners accepting permanent contraception, the percentage of women who finished their family with only female children and comparison of practice observed in rural and urban population. Methods: A retrospective analytical study was conducted at RKDF medical college and research centre Bhopal M.P. from 1 January 2017 to 31 August 2020 (3 Years 7 months) on 286 patients. Data of the patients who had undergone tubal ligation after normal vaginal delivery, caesarean section, with medical termination of pregnancy and interval tubectomy was collected at RKDF medical college and research centre Bhopal M.P. Results: Parity wise maximum number of cases completed their family with two issues i.e. (51%). Permanent sterilisation was done in even one issue in (0.6%) minimum number of cases were observed in 9 issues (0.34%). Rural versus urban distribution was 25 and 75% respectively. Maximum age observed was 47 years of husband and 42 years of wife. Conclusions: For the desire of male child, number of female children increased thereby increasing the family size.